2015
DOI: 10.1002/jpln.201400658
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal influence of olive mill wastewater applications on an orchard soil under semi‐arid conditions

Abstract: Olive oil production generates large amounts of olive mill wastewater (OMW). OMW has a high nutrient content and could serve as fertilizer, but its fatty and phenolic constituents induce soil water repellency, phytotoxicity, and acidification. An appropriate season of OMW application may mitigate negative consequences while preserving beneficial effects. In order to investigate this, a field study was conducted, in which OMW was applied to an olive orchard in Israel either in winter or summer. Soil-water inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
5
17
0
Order By: Relevance
“…The secondary increase in salinity and SPC in SP and SU dry plots during the summer season 2012 suggests an upward directed water flow within the soil profile due to evaporation at the surface layer (Magdich et al, 2013) by which OMW compounds migrated upward by capillary action (Steinmetz et al, 2015). This matches with the clearly upward directed hydraulic gradient down to 50 cm depth in these plots (Fig.…”
Section: Long-term Omw-soil Interaction and Transport Mechanismssupporting
confidence: 71%
See 3 more Smart Citations
“…The secondary increase in salinity and SPC in SP and SU dry plots during the summer season 2012 suggests an upward directed water flow within the soil profile due to evaporation at the surface layer (Magdich et al, 2013) by which OMW compounds migrated upward by capillary action (Steinmetz et al, 2015). This matches with the clearly upward directed hydraulic gradient down to 50 cm depth in these plots (Fig.…”
Section: Long-term Omw-soil Interaction and Transport Mechanismssupporting
confidence: 71%
“…Other studies showed a rapid decrease in phenolic compounds (Di Serio et al, 2008) and degradation to almost 50% of their initial concentration within the first 2 -3 weeks following OMW application to soil (Saadi et al, 2007a;Sierra et al, 2007;Tsiknia et al, 2014). No such effect was observed when OMW was applied in the winter season (Steinmetz et al, 2015), not even in a depth of 2 m (Chartzoulakis et al, 2010) after one single OMW application during one year study. On the other hand, soluble phenolic compounds were observed in soil at 1.25 m depth during the winter season (Sierra et al, 2001) and phenolic monomers were detected at a depth of 1.2 m one year after OMW spreading on soil (Mekki et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is possible that the irrigation in Gilat suppressed the development of water repellency and increased transport of hydrophobic compounds [60]. Also, Steinmetz et al [61] found a significant effect of irrigation towards water repellency. The stronger persistence of the elevated WDPT in Bait Reema indicates that hydrophobizing compounds like grease, oil and OMW organic matter remained in the upper soil layer [62] and that water repellency has the potential to persist even after one single OMW treatment.…”
Section: Effects Of Omw and Water Application On Soil Propertiesmentioning
confidence: 99%